An Analysis Of Budget Realization Report Of The Regional Revenue Agency At Seluma Regency - Sari , Risna Purnama; Susanti , Neri; Kresnawati , Kresnawati (Utami Publisher, 2025)
The purpose of the study was to determine and analyze the effectiveness of Regional Original Revenue (PAD) and the efficiency of the Budget Realization Report (LRA) expenditure budget at the Seluma Regency Regional Revenue Agency (BAPENDA) for the 2021 fiscal year and 2022 fiscal year. The method used is Quantitative descriptive using effectiveness and efficiency ratios. The results of the research conducted show that the effectiveness ratio of Regional Original Revenue (PAD) for the 2021 fiscal year is quite effective with a percentage of 91.48% while the 2022 fiscal year is ineffective with a percentage of 74.1% and the average effectiveness ratio is less effective with a ratio of 82.79%. The efficiency ratio of the expenditure budget in fiscal year 2021 shows efficient criteria with a percentage of 71.04% and fiscal year 2022 shows quite efficient criteria with a percentage of 82.1% and the average efficiency ratio is efficient with a percentage of 76.57%. With the level and criteria determined and the target to be achieved, Bapenda Seluma Regency cannot be categorized as highly effective and highly efficient financial performance because the PAD effectiveness ratio and the expenditure budget efficiency ratio have decreased in fiscal year 2022.